2003
DOI: 10.1046/j.1474-8673.2003.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic innervation of immune organs and neuroimmune modulation

Abstract: 1. Increasing evidence indicates the occurrence of functional interconnections between immune and nervous systems, although data available on the mechanisms of this bi-directional cross-talking are frequently incomplete and not always focussed on their relevance for neuroimmune modulation. 2. Primary (bone marrow and thymus) and secondary (spleen and lymph nodes) lymphoid organs are supplied with an autonomic (mainly sympathetic) efferent innervation and with an afferent sensory innervation. Anatomical studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
148
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 203 publications
(338 reference statements)
0
148
1
3
Order By: Relevance
“…Our results indicate that Ag recognition by naive CD4 + T cells induces DRD3 expression, rendering this population sensible to this neurotransmitter during the activation/differentiation process. In a physiologic context, DRD3 expressed on recently activated CD4 + T cells may be stimulated by DA released by neighboring dendritic cells present in the lymph node, or by sympathetic dopaminergic terminals reported to innervate both primary and secondary lymphoid organs (32)(33)(34). The latter option seems the most likely, considering that we detect DRD3 expression on CD4 + T cells between 2 and 3 d after activation and that studies using intravital microscopy have shown that in vivo-activated CD4 + T cells reduce their interaction with dendritic cells after 40 h of residence in the lymph node (35).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that Ag recognition by naive CD4 + T cells induces DRD3 expression, rendering this population sensible to this neurotransmitter during the activation/differentiation process. In a physiologic context, DRD3 expressed on recently activated CD4 + T cells may be stimulated by DA released by neighboring dendritic cells present in the lymph node, or by sympathetic dopaminergic terminals reported to innervate both primary and secondary lymphoid organs (32)(33)(34). The latter option seems the most likely, considering that we detect DRD3 expression on CD4 + T cells between 2 and 3 d after activation and that studies using intravital microscopy have shown that in vivo-activated CD4 + T cells reduce their interaction with dendritic cells after 40 h of residence in the lymph node (35).…”
Section: Discussionmentioning
confidence: 99%
“…Decentralization of autonomic system to lymphoid organs including spleen may be an important factor in disruption of immune response. 6 SCI patients may have muted neutrophil phagocytosis, natural killer cell cytotoxicity and T-lymphocyte activation compared with healthy controls. 7 Furthermore, degree of reduced phagocytosis and impaired B-cell functions may be correlated with level of SCI injury.…”
Section: Discussionmentioning
confidence: 99%
“…B cells were purified by negative selection using a mouse B cell enrichment mixture (StemCell Technologies) that contained Abs directed against mouse CD4, CD8, CD11b, myeloid differentiation Ag Gr-1, and erythroid Ag TER 119, as well as dense particles that were covalently coated with a second Ab. B cell purity was found to be Ͼ90%, which was confirmed by immunocytochemistry using HRP-labeled sheep anti-mouse IgG F(abЈ) 2 (1/100 dilution; Amersham Biosciences). Cell viability in both cases was found to be Ͼ85% as assessed by the trypan blue exclusion test.…”
Section: Adoptive Transfer Of T and B Cellsmentioning
confidence: 97%
“…Two weeks later, immunohistochemistry was performed on the spleens of these animals using anti-CD3, anti-IgG F(abЈ) 2 , and TH Abs. FACS analysis was also performed using splenic cells prepared as mentioned above.…”
Section: Adoptive Transfer Of T and B Cellsmentioning
confidence: 99%
See 1 more Smart Citation